Cardiomyocyte-derived small extracellular vesicles can signal eNOS activation in cardiac microvascular endothelial cells to protect against Ischemia/Reperfusion injury - Chen, Guihao (Theranostics, 2020)
Rationale: The crosstalk between cardiac microvascular endothelial cells (CMECs) and cardiomyocytes (CMs) has emerged as a key component in the development of, and protection against, cardiac diseases. For example, activation of endothelial nitric oxide synthase (eNOS) in CMECs, by therapeutic strategies such as ischemic preconditioning, plays a critical role in the protection against myocardial ischemia/reperfusion (I/R) injury. However, much less is known about the signals produced by CMs that are able to regulate CMEC biology. Here we uncovered one such mechanism using Tongxinluo (TXL), a traditional Chinese medicine, that alleviates myocardial ischemia/reperfusion (I/R) injury by activating CMEC eNOS. The aim of our study is to identify the signals produced by CMs that can regulate CMEC biology during I/R. Methods: Ex vivo, in vivo, and in vitro settings of ischemia-reperfusion were used in our study, with the protective signaling pathways activated in CMECs identified using genetic inhibition (p70s6k1 siRNA, miR-145-5p mimics, etc.), chemical inhibitors (the eNOS inhibitor, L-NNA, and the small extracellular vesicles (sEVs) inhibitor, GW4869) and Western blot analyses. TritonX-100 at a dose of 0.125% was utilized to inactivate the eNOS activity in endothelium to investigate the role of CMEC-derived eNOS in TXL-induced cardioprotection. Results: We found that while CMEC-derived eNOS activity was required for the cardioprotection of TXL, activation of eNOS in CMECs by TXL did not occur directly. Instead, eNOS activation in CMECs required a crosstalk between CMs and CMECs through the uptake of CM-derived sEVs. We further demonstrate that TXL induced CM-sEVs contain increased levels of Long Intergenic Non-Protein Coding RNA, Regulator Of Reprogramming (Linc-ROR). Upon uptake into CMECs, linc-ROR downregulates its target miR-145-5p leading to activation of the eNOS pathway by facilitating the expression of p70s6k1 in these cells. The activation of CMEC-derived eNOS works to increase survival in both the CMECs and the CMs themselves. Conclusions: These data uncover a mechanism by which the crosstalk between CMs and CMECs leads to the increased survival of the heart after I/R injury and point to a new therapeutic target for the blunting of myocardial I/R injury.